Achievement rate and predictive factors of the recommended therapeutical target in patients with axial spondyloarthritis who remain on biological therapy: a prospective cohort study in Spain - Alejandro Balsa; Victoria Navarro-Compán; Laura Nuño; Karen Franco-Gómez; Diana Peiteado; Irene Monjo; Alejandro Villalba; Patricia Bogas; Diego Benavent; Marta Novella-Navarro; Chamaida Plasencia-Rodríguez; Romina Nieto (BMJ Open, 2022)
Objectives To determine the frequency of sustained remission (R) or low diseas activity (LDA) in patients with axial spondyloarthritis (axSpA) undergoing long-term biological therapy and to analyse predictive factors for achieving these outcomes.Design Prospective, observational cohort study.Setting Spanish hospital.Participants Patients with axSpA who initiated biological treatment between 2003 and 2017.Intervention Assessment of demographic and clinical characteristics at the beginning of treatment and disease activity every 6 months up to a maximum of 2 years.Main outcome measures Disease activity was measured by Ankylosing Spondylitis Disease Activity Score (ASDAS) and Bath Ankylosing Spondylitis Disease Activity Index and C reactive protein (BASDAI&CRP). Sustained R was defined as ASDAS<1.3 and/or BASDAI <2 and normal CRP while sustained LDA was defined as ASDAS <2.1 and/or BASDAI <4 and normal CRP on at least three consecutive visits.Results In total 186 patients (66.1% men and 75.3% with radiographic sacroiliitis) were included. Overall, 76.8% of patients achieved ASDAS R/LDA (R53.2%/LDA23.6%) in at least one visit. Forty per cent (R17.6%/LDA22.4%) of the patients fulfilled the sustained ASDAS R/LDA state, whereas only 30.8% maintained this status (R14.8%/LDA15.9%) according to BASDAI&CRP. In the multivariate analysis, male sex (OR=4.01), younger age at the beginning of biological therapy (OR=0.96) and an HLA*B27 positive status (OR=4.30) were associated with achieving sustained ASDAS R/LDA.Conclusions In clinical practice, around one-third of patients on biological disease-modifying antirheumatic drugs achieve a sustained R/LDA status, but these rates drop to less than one in five when targeting remission, preventing the use of the latter as a feasible target. Male sex, HLA*B27 positivity and younger age at the beginning of biological therapy are the main predictors for achieving sustained R/LDA.